Ecotypic variation for seed dormancy, longevity and germination requirements in wild/weedy Sorghum bicolor in Ethiopia: implications for seed mediated transgene dispersal and persistence - Adugna, Asfaw (Springer International Publishing AG, 2013)
Seed dispersal is one of the vehicles of gene flow in plants. If a seed carrying transgene(s) is dispersed into the environment, the fate can be determined by its persistence in the soil bank, which can also vary in different ecotypes of a species and the physical environment of the soil including temperature and moisture. This study aimed at investigating ecotypic differences in wild sorghum for dormancy and longevity and their response to varying levels of temperature and moisture for seed germination to aid efforts to predict the potential risk of transgene flow via seeds and persistence in the soil. Wild sorghum seed was collected from different geographical regions in Ethiopia and buried for a maximum of 24 months in the soil. In a separate study, three levels of constant temperature and five levels of osmotic potential (Ψ(s)) were used to investigate variation in wild sorghum ecotypes for seed germination. Viability of buried seeds declined over time, but the rate of decline differed among ecotypes. Better seed longevity was observed at 20 cm soil depth than 10 cm in two wild sorghum ecotypes. Crop seeds depleted within the first six months regardless of the burial depth whereas on the average 1.24% viability was observed in wild sorghum seed after 24 months of burial in the soil. Ecotypic differences were also evident in response to varying temperature and Ψ(s). Therefore, dispersed seeds carrying crop genes (including transgenes) could persist in the soil for considerable period of time, which may have implications for transgene flow and persistence. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/2193-1801-2-248) contains supplementary material, which is available to authorized users.